2017
DOI: 10.1111/liv.13526
|View full text |Cite
|
Sign up to set email alerts
|

IFNL4 rs368234815 and rs117648444 variants predict off‐treatment HBsAg seroclearance in IFN‐treated HBeAg‐negative chronic hepatitis B patients

Abstract: IFNL4 rs368234815 and rs117648444 functional variants are worth to be investigated as pretreatment combined predictors of IFN response in HBeAg-negative CHB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Because only the rs368234815-dG allele provides functional significance to rs117648444, this marker should not be tested alone. The combination of rs368234815 and rs117648444 improved and explained the association with viral clearance and expression of interferon-stimulated genes, providing support for the primary causal role of IFN-λ4 and its variants in these associations (Galmozzi and Aghemo 2014; Terczynska-Dyla and others 2014; Bhushan and others 2017; Bhushan and Chinnaswamy 2018; Galmozzi and others 2018).…”
Section: Introductionmentioning
confidence: 85%
“…Because only the rs368234815-dG allele provides functional significance to rs117648444, this marker should not be tested alone. The combination of rs368234815 and rs117648444 improved and explained the association with viral clearance and expression of interferon-stimulated genes, providing support for the primary causal role of IFN-λ4 and its variants in these associations (Galmozzi and Aghemo 2014; Terczynska-Dyla and others 2014; Bhushan and others 2017; Bhushan and Chinnaswamy 2018; Galmozzi and others 2018).…”
Section: Introductionmentioning
confidence: 85%
“…IFNλ4 rs368234815 and rs117648444 variants were reported to strongly predict HBsAg clearance in 126 HBeAg-negative patients treated with IFN and followed up for a median of 11 years. 11 This study reported that the 15-year cumulative probability of HBsAg loss in the 62 carriers of the rs368234815 TT/TT genotype, which abolishes IFNλ4 protein production and in the 19 patients carrying the rs117648444 T allele, which produces an impaired IFNλ4-S70 protein, was significantly higher than in the 45 subjects who encoded only the fully functional IFNλ4-P70 (42% vs 11%, P = .003).…”
Section: Key Pointsmentioning
confidence: 80%
“…However, the preliminary observations of an association between favorable IFNλ4 polymorphisms and increased chances of a sustained virological and serological response in both HBeAg‐positive and ‐negative patients were not confirmed in subsequent studies . Recently, IFNλ4 rs368234815 and rs117648444 variants were reported to strongly predict HBsAg clearance in 126 HBeAg‐negative patients treated with IFN and followed up for a median of 11 years . This study reported that the 15‐year cumulative probability of HBsAg loss in the 62 carriers of the rs368234815 TT/TT genotype, which abolishes IFNλ4 protein production and in the 19 patients carrying the rs117648444 T allele, which produces an impaired IFNλ4‐S70 protein, was significantly higher than in the 45 subjects who encoded only the fully functional IFNλ4‐P70 (42% vs 11%, P = .003).…”
Section: Peg‐ifn In Nuc‐naïve Patientsmentioning
confidence: 94%
“…However, a three-way interaction was identified between IFNL4/HLA-DQ and HBV infection with a multifactor dimensionality reduction test ( Fan et al, 2016 ). Two SNPs and in the IFNL4 gene, which was also analyzed in this study, could predict IFN treatment response in HBeAg-negative HBV patients ( Galmozzi et al, 2018 ). Similar to our results, SNPs in the IFNL4 gene could not influence the reaction of Thai HBV patients to PEG-IFN ( Limothai et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%